PRAWO I SĄDY NA LITWIE W 1812 ROKU W ŚWIETLE „DZIENNIKA CZYNNOŚCI TYMCZASOWEGO RZĄDU LITEWSKIEGO” - Godek, Sławomir (Zeszyty Prawnicze, 2016)
THE LAW AND THE COURTS IN LITHUANIA IN 1812 IN THE LIGHT OF THE OFFICIAL JOURNAL OF THE ACTIVITIES OF THE PROVISIONAL GOVERNMENT OF LITHUANIA Summary At the very beginning of his Russian campaign of 1812 Napoleon created a somewhat complicated structure for the new administration of Lithuania. A key element in it was the Commission of the Provisional Government of Lithuania, a surrogate Lithuanian government. Virgilijus Pugačiauskas has recently published the Commission’s official journal, Dziennik czynności Komisji Tymczasowego Rządu Litwy, for the period from 2 July 1812 to 30 July 1813 from the manuscript. In the light of this invaluable resource, we can see the Commission’s efforts to build a new administration and revenue services, create a Lithuanian army, and ensure supplies for Napoleon’s forces. One of the important tasks undertaken by the Commission was to restore the judiciary, which had been disorganised by the war, and to ensure the normal administration of justice and the restoration of full power to the Statute of Lithuania, which had been in use under the Polish-Lithuanian Commonwealth and had already been partially supplanted by Russian law following the Partitions of Poland-Lithuania. An act which was of fundamental importance in this respect was the institution of a set of regulations for the judiciary Prawidła dla sądownictwa, adopted by the Commission on 29 July, 1812. Under this act the courts were temporarily to resume their activities only in criminal cases, on the grounds of Lithuanian law and using Polish as the official language. The Commission reserved the right to approve death sentences and – as may be seen from the minutes – actually used this power. The contents of the protocols indicate that the courts actually resumed operations in early August 1812. In October 1812 the Commission adopted a measure on the new organisation of the Vilnius municipal courts.